The Determinants of non Performing Loans: Do Institutions Matter? A Comparative Analysis of the Middle East and North Africa (MENA) and Central and Eastern European (CEE) Countries - RACHID, Semia (Journal of Advanced Studies in Finance, 2020)
This paper tries to study the determinants of non-performing loans (NPL) in the Middle East and North Africa (MENA) and Central and Eastern European (CEE) countries during the 1997-2016 period. Our analysis, which is based on different panel data estimation approaches, shows that institutions have different effects on the level of NPL in the MENA and the CEE countries. We found that institutions (rule of law) increase the level of NPL in the MENA countries but they decrease these loans in the CEE countries. This result is attributed to the existence of an institutional difference between both samples of countries. In fact, the rise of NPL in the CEE countries is attributed to financial development.  On the other hand, the global financial crisis (GFC) has an important effect on the accumulation of NPL in the MENA countries. However, the relationship between the GFC and the NPL is not significant for the CEE countries.